2018
DOI: 10.1101/485151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Speeding up anterior-posterior patterning of insects by differential initialization of the gap gene cascade

Abstract: Recently, it was shown that anterior-posterior patterning genes in the red flour beetle Tribolium castaneum are expressed sequentially in waves. However, in the fruit fly Drosophila melanogaster, an insect with a derived mode of embryogenesis compared to Tribolium, anterior-posterior patterning genes quickly and simultaneously arise as mature gene expression domains that, afterwards, undergo slight posterior-to-anterior shifts. This raises the question of how a fast and simultaneous mode of patterning, like th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…This proposal is motivated by the recent suggestion in insects that different sets of enhancers control waves of gap genes at different phases of embryonic growth ( El-Sherif and Levine, 2016 ). Such assumptions explain the so-called ‘speed-gradient’ model suggested to explain the gene expression wave dynamics observed during AP patterning in the beetle Tribolium ( Zhu et al, 2017 ) (see Figure 1—figure supplement 2 ) and (with some additional assumptions) the more subtle gene expression dynamics observed during AP patterning in Rudolf et al, 2020 ; El-Sherif and Levine, 2016 . Using both gene-network and geometric formalisms, we characterize the types of bifurcations found in systems transitioning from a dynamic to a static regime.…”
Section: Introductionmentioning
confidence: 92%
“…This proposal is motivated by the recent suggestion in insects that different sets of enhancers control waves of gap genes at different phases of embryonic growth ( El-Sherif and Levine, 2016 ). Such assumptions explain the so-called ‘speed-gradient’ model suggested to explain the gene expression wave dynamics observed during AP patterning in the beetle Tribolium ( Zhu et al, 2017 ) (see Figure 1—figure supplement 2 ) and (with some additional assumptions) the more subtle gene expression dynamics observed during AP patterning in Rudolf et al, 2020 ; El-Sherif and Levine, 2016 . Using both gene-network and geometric formalisms, we characterize the types of bifurcations found in systems transitioning from a dynamic to a static regime.…”
Section: Introductionmentioning
confidence: 92%
“…This proposal is motivated by the recent suggestion in insects that different sets of enhancers control waves of gap genes at different phases of embryonic growth (El-Sherif & Levine, 2016). Such assumptions explain the so-called "speed-gradient" model suggested to explain the gene expression wave dynamics observed during AP patterning in the beetle Tribolium (Zhu et al, 2017) (see Figure 1-figure supplement 2) and (with some additional assumptions) the more subtle gene expression dynamics observed during AP patterning in (Rudolf, Zellner, & El-Sherif, 2020). Using both gene-network and geometric formalisms, we characterize the types of bifurcations found in systems transitioning from a dynamic to a static regime.…”
mentioning
confidence: 97%
“…Hence, new models of embryonic pattern formation need to be adopted, and concomitantly, new models of how enhancers work within these pattern formation models. Some of the authors have recently suggested a model that explains the generation of either periodic or non-periodic waves of gene expressions speed model (6,23,24,30,34). In this model, a morphogen gradient modulates the speed of either a molecular clock (to produce a periodic pattern) or a genetic cascade (to produce a non-periodic pattern).…”
Section: Introductionmentioning
confidence: 99%
“…In the flour beetle Tribolium castaneum ( Tribolium ), it has been shown that both pair-rule and gap genes are expressed as dynamic waves that propagate from posterior to anterior (2024), much like how segmentation and Hox genes are expressed in vertebrates (6). Even pair-rule and gap genes in Drosophila , classically thought to be expressed stably, have recently been shown to undergo dynamic posterior-to-anterior shifts (25–29), a phenomenon that has been suggested to be an evolutionary vestige of outright gene expression waves (6,3033).…”
Section: Introductionmentioning
confidence: 99%